2021
DOI: 10.3390/en14123588
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Thermal Performance of Different Fruit Packaging Box Designs

Abstract: Packaging was recently identified as an essential element in addressing the key challenge of sustainable food supply and is gaining interest among researchers. It is a central element in food quality preservation due to its role in heat and mass exchange with the external atmosphere, contributing to the preservation of food quality during storage and extending food shelf life. This work proposes three new packaging configurations with the same size but different geometry and ventilation hole sizes and geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The fruit model considers solid zones with two different solid properties, polystyrene and fruit models, as shown in Figure 3b. This condition was required to simulate the experimental set-up described in [17][18][19][20]. As the buoyancy and radiation effects are assumed negligible, they are not taken into account.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit model considers solid zones with two different solid properties, polystyrene and fruit models, as shown in Figure 3b. This condition was required to simulate the experimental set-up described in [17][18][19][20]. As the buoyancy and radiation effects are assumed negligible, they are not taken into account.…”
Section: Computational Modelmentioning
confidence: 99%
“…Predictions are monitored and data are exported at the end of each hour of simulation. The simulation time was set to 8 h because in the experimental tests performed there were no temperature changes at the end of this time [17][18][19][20]. The numerical simulation took around 16 h to converge, being performed on an Intel ® Xeon ® CPU @ (3.47 GHz) with 256 GB of RAM.…”
Section: Simulation Setupmentioning
confidence: 99%
“…This diversification of PCM categories allows for a wide range of potential applications, tailoring their usage according to the specific thermal management requirements. Several studies have explored the thermal performance of various fruit packaging crates [22][23][24][25][26]. Studies also analyzed the utility of PCM pouches for active and intelligent packaging [27,28], and the measurement of temperatures and relative humidity during the transportation of horticultural goods [8].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, reference [24] provides experimental evidence of the thermal response of two types of food alveoli, comparing their performance with and without the integration of PCM. The authors demonstrated that aluminum foil alveoli, in conjunction with PCM, delayed the heating process effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate packaging can reduce the physical damage of the fruit during transportation and ensure a better appearance [9]. At present, mangoes are packaged in polyethylene foam mesh sleeves, and placed in polystyrene foam boxes, except for high-end consumer products.…”
Section: Introductionmentioning
confidence: 99%